Transitioning from NAFLD to MAFLD and MASLD: the toxic relationship with alcohol consumption - Ozercan, Mubin; Tawheed, Ahmed; El-Kassas, Mohamed (Open Exploration Publishing Inc, 2025)
Alcohol is a well-known toxic etiologic factor for liver injury. Metabolic substrates of alcohol (especially acetaldehyde) have a major responsibility and genetic susceptibility, alterations in microbiota and immune system are important co-factors for this injury. Major injury in liver is hepatocellular lipid accumulation. Therefore the relationship between non-alcoholic and alcoholic fatty liver diseases should have been defined clearly. Recently two major liver committees adopted new terminologies such as metabolic-associated fatty liver disease (MAFLD), metabolic dysfunction-associated steatotic liver disease (MASLD), metabolic dysfunction and alcohol-related liver disease (MetALD), and alcoholic liver disease (ALD) instead of non-alcoholic fatty liver disease (NAFLD). These terminologies were based on the effects of metabolic syndrome on liver. Alcohol consumption was defined differently according to these nomenclatures. MAFLD defined alcohol intake (regardless of amount) as “dual etiology fatty liver disease” and the Delphi consensus defined MASLD, MetALD, or ALD according to daily consumption of alcohol amount. © The Author(s) 2025.
Keywords: alcohol consumption; alcoholic liver disease; metabolic dysfunction-associated fatty liver disease; Metabolic dysfunction-associated steatotic liver disease; non-alcoholic fatty liver disease